1982
DOI: 10.1038/bjc.1982.236
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of melphalan activity against a murine tumour by nitroimidazole compounds

Abstract: Summary.-The activity against murine anaplastic MT tumours of the chemotherapeutic agent melphalan, either alone or in combination with one of 6 nitroimidazole compounds, was assayed using an in vivo-in vitro tumour excision assay. The melphalan alone proved cytotoxic to the tumour, whereas relatively little cytotoxicity was produced by any of the nitroimidazoles alone. When the nitroimidazole were given in combination with melphalan, dose-modifying potentiation of its cytotoxicity was observed. Maximum potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Most of these combination studies have been concerned with MISO. Recently it has been shown that other nitro compounds can show potentiating activity considerably greater than MISO (Workman & Twentyman, 1982;Sheldon et al, 1982). In one of these studies (Sheldon et al, 1982) Appendix RSU 1069 gave satisfactory elemental and mass spectural analyses.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Most of these combination studies have been concerned with MISO. Recently it has been shown that other nitro compounds can show potentiating activity considerably greater than MISO (Workman & Twentyman, 1982;Sheldon et al, 1982). In one of these studies (Sheldon et al, 1982) Appendix RSU 1069 gave satisfactory elemental and mass spectural analyses.…”
Section: Discussionmentioning
confidence: 88%
“…L MT tumour implanted intramuscularly (Sheldon et al, 1982). This study showed that the compound Ro 03-8799 produced the greatest potentiation.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…seen in every study: A threshold dose of 300-500mgkg-1 seems to be needed. Only two studies at doses of 500 mg kg-1 or below have demonstrated chemosensitization (Rose et al, 1980;Sheldon et al, 1982) and two other studies have shown no effect at 500mgkg-1 (Fu et al, 1981;Twentyman & Workman, 1982). Far fewer studies have been published using chronic MISO with melphalan.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the chemosensitizing activity of MISO and MTR (Sheldon et al, 1982;Twentyman & Workman, 1982;Milas et al, 1983), it was observed in in vivo experiments with murine tumours that antitumour drugs, i.e., hydroxyurea, cyclophosphamide, melphalan, adriamycin, etc. had an enhanced effect when given with MISO or MTR, though MTR is less active than MISO (Twentyman & Workman, 1982), while little effect was seen with CDDP, vincristine, 5-FU, and bleomycin.…”
mentioning
confidence: 99%